Measuring tax administrations efficiency using data envelopment analysis: evidence from 26 European countries. (21st October 2022) - Anastasiou, Athanasios; Kalligosfyris, Charalampos; Kalamara, Eleni
The purpose of this paper is to assess the efficiency of tax administrations of 26 European countries, using data envelopment analysis. In particular, by applying the CCR data environment analysis (DEA) output-oriented model, the quantification of the tax administrations performance of 26 European countries is attempted in the areas of taxpayers' servicing, public revenue collection, strengthening voluntary tax compliance and targeted tax audits, the assessment of relative efficiency, the evaluation of results and the identification of fully efficient and inefficient tax administrations, in which a real improvement in their efficiency can be achieved. Subsequently, for the tax administrations that are assessed as inefficient, the reference units are identified, the missing quantity of outputs and the excess amount of inputs are estimated, in order to make them efficient and a set of possible ways of improving their operation is proposed, through specific changes.